2021
DOI: 10.15252/embj.2020107206
|View full text |Cite
|
Sign up to set email alerts
|

Tumor cell heterogeneity and its transcriptional bases in pancreatic cancer: a tale of two cell types and their many variants

Abstract: Pancreatic ductal adenocarcinoma (PDAC), one of the most highly lethal tumors, is characterized by complex histology, with a massive fibrotic stroma in which both pseudo‐glandular structures and compact nests of abnormally differentiated tumor cells are embedded, in different proportions and with different mutual relationships in space. This complexity and the heterogeneity of the tumor component have hindered the development of a broadly accepted, clinically actionable classification of PDACs, either on a mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 98 publications
(159 reference statements)
0
13
0
Order By: Relevance
“…The notion that cancer cells can dynamically switch from one state to another in response to environmental stresses and therapeutic pressure without genomic alterations is gaining greater recognition (Pogrebniak & Curtis, 2018; Mills et al , 2019; Boumahdi & de Sauvage, 2020) (discussed in other reviews of this series by Milan et al , 2021). This phenomenon, termed cell plasticity, is characterised by a fundamental change in the biological properties of the cell occurring as a consequence of dynamic and reversible epigenetic and transcriptional changes (in sharp contrast to genetic alterations, which have binary and largely irreversible effects) (Calabrese et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The notion that cancer cells can dynamically switch from one state to another in response to environmental stresses and therapeutic pressure without genomic alterations is gaining greater recognition (Pogrebniak & Curtis, 2018; Mills et al , 2019; Boumahdi & de Sauvage, 2020) (discussed in other reviews of this series by Milan et al , 2021). This phenomenon, termed cell plasticity, is characterised by a fundamental change in the biological properties of the cell occurring as a consequence of dynamic and reversible epigenetic and transcriptional changes (in sharp contrast to genetic alterations, which have binary and largely irreversible effects) (Calabrese et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We envisage that the opposite effects of SFK on KRAS and YAP provide a flexible mechanism that enables PDAC cells to initiate EMT and metastasis when SFK/YAP signaling predominates and explain coexistence of different subtypes of PDAC in different locations of the same tumor. Indeed, well-differentiated and poorly differentiated (basal-like/squamous) PDAC cells coexist in variable proportions in most PDACs [82].…”
Section: Discussionmentioning
confidence: 99%
“…Additional analysis using physical or virtual separation of cell types within the tumors, is subdividing the two major subtypes of PDAC in additional subgroups [79,80]. Recent studies using singlecell and single-nucleus RNA-seq, as well as pancreatic organoids [81], support the notion that the classical and basal-like/squamous PDAC cells coexist in variable proportions in most PDACs (reviewed in [82] and references therein). Accordingly, recent studies showed coexistence of basal-like and classical subtypes within individual PDAC tumors [79,83].…”
Section: Pdac Subtypes and Kras Dependencymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite advances in surgical and systemic treatment, the 5-year overall survival (OS) rate remains approximately 10% [ 4 ]. This low survival rate is mostly caused by late detection of disease due to the late onset of symptoms [ 5 ]. Therefore, most patients are diagnosed with advanced stage disease, and only a minority (15–20%) of patients are eligible for treatment with curative intent [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%